A EXPRESSÃO DO LIBERALISMO NA REVISTA A ESCOLA (1906-1910) NO PARANÁ - Zanlorenzi, Claudia Maria Petchak (2014)
This Thesis presents a study on Brazilian education in the early twentieth century, whose primary source is The School journal, which had been published in Curitiba, PR, between 1906 and 1910, and whose objective is to discuss the spread of liberal ideology in Brazil during early Republican. Specifically, we have proposed to identify the influences of liberalism on education, on changes in teaching and on spreading the intuitive method as an ideal model of education. From the assumption of historical materialism, the methodological procedures adopted in the research went trhough the following steps: literature review, survey and cataloging of The School journal in the Public Archives of Paraná and Public Library located in Curitiba,selection of relevant articles to the research development, analysis and discussion of the selected articles, searching for the objectives of the proposed research and for writing the thesis organized into three parts. In the first section, we addressed, Firstly we have approached the principles of liberalism, based on the classical authors Locke and Smith, in order to demonstrate liberalism as a philosophical and political foundation, as well as its use as an ideology. Then we have analyzed the relationship between liberalism and State and its dissemination in Brazil after the proclamation of the Republic. We have also addressed the liberalism in education, having as source The School journal, by approaching specifically the school education as redefinition of the free worker and its using as a priority strategic based on Liberal Education during the Brazilian first Republic. Our efforts culminate with a discussion about teaching and the intuitive method as a way of homogenizing this proposal. The reflections that come up from the study of The School journal have pointed the speeches, the yearnings, the conveniences, the interests of society over education, and have provided clues about the repercussions and controversy introduced, and even more, have greatly contributed to the understanding of contemporary situations. The present study results’ have allowed us to conclude that education in Paraná State in the early twentieth century was marked by liberal ideology influences, which was widely disseminated in the pages of The School journal.